Governance of Health Care Services: A Critical Understanding of Federal Experiences from Central Nepal - Dahal, Kapil Babu (Molung Educational Frontier, 2020)
People in different locality interact, perceive, and experience the government and governance through the government’s various service delivery mechanisms mainly, which affect them in their locale. Governance in the health sector can serve as an essential and critical window through which we can glance at the situation of governance in a given society. Multiple voices from the actors involved in delivering health care services and health service users portray the current emerging situation of health governance, especially, during the initial years of implementation of federal system in Nepal. In portraying the current health governance scenario in the study areas, this article shows how people’s experience of forms of governance affects their uptake of health care services. It uses micro-level ethnographic information to look at the broader issue of health governance.